Studying dynamics of a cantilever bar with variable bending stiffness - Khabidolda, O.; Akhmediyev, S.K.; Vatin, N.I.; Abeuova, L.; Nurgoziyeva, A. (JMMCS, 2023)
In this paper, there are studied the dynamic processes (free and forced oscillations) of isotropic cantilever plates in the form of an isosceles (wedge-shaped) triangle. In the study, the finite difference method has been applied using a regular one-dimensional (linear) grid. The finitedifference equations developed by the authors for point-distributed masses along the length of the wedge are presented, taking into account the linearly variable bending stiffness. On this basis, the results of studies in the form of amplitude-frequency characteristics (frequencies, dynamic forces and deflections) in the resonant and near-resonant regions have been obtained. The content of theoretical provisions and applied results can be widely used in the scientific and engineering fields and in the field of mechanics of structures.
Keywords: triangular plate; numerical method; grid method; dynamic deflections and forces; variable bending stiffness; bar analogy; frequency spectrum; amplitude-frequency characteristics